Snow disappearance timing is dominated by forest effects on snow accumulation in warm winter climates of the Pacific Northwest, United States. Issue 10 (11th April 2017) - Dickerson‐Lange, Susan E.; Gersonde, Rolf F.; Hubbart, Jason A.; Link, Timothy E.; Nolin, Anne W.; Perry, Gwyneth H.; Roth, Travis R.; Wayand, Nicholas E.; Lundquist, Jessica D.
Abstract: Forests modify snow processes and affect snow water storage as well as snow disappearance timing. However, forest influences on snow accumulation and ablation vary with climate and topography and are therefore subject to temporal and spatial variability. We utilize multiple years of snow observations from across the Pacific Northwest, United States, to assess forest–snow interactions in the relatively warm winter conditions characteristic of maritime and transitional maritime–continental climates. We (a) quantify the difference in snow magnitude and disappearance timing between forests and open areas and (b) assess how forest modifications of snow accumulation and ablation combine to determine whether snow disappears later in the forest or in the open. We find that snow disappearance timing at 12 (out of 14) sites ranges from synchronous in the forest and open to snow persisting up to 13 weeks longer in the open relative to a forested area. By analyzing accumulation and ablation rates up to the day when snow first disappears from the forest, we find that the difference between accumulation rates in the open and forest is larger than the difference between ablation rates. Thus, canopy snow interception and subsequent loss, rather than ablation, set up longer snow duration in the open. However, at two relatively windy sites (hourly average wind speeds up to 8 and 17 m/s), differential snow disappearance timing is reversed: Snow persists 2–5 weeks longer in the forest. At the windiest sites, accumulation rates in the forest and open are similar. Ablation rates are higher in the open, but the difference between ablation rates in the forest and open at these sites is approximately equivalent to the difference at less windy sites. Thus, longer snow retention in the forest at the windiest sites is controlled by depositional differences rather than by reduced ablation rates. These findings suggest that improved quantification of forest effects on snow accumulation processes is needed to accurately predict the effect of forest management or natural disturbance on snow water resources.